Dinamika Penyebaran dan Perkembangan Islam di Desa Pagaran Bira Jae, Kabupaten Padang Lawas, Sumatera Utara - Harahap, Afif Wira Handika; Achiriah, Achiriah; Harahap, Nursapia (Local History & Heritage, 2024)
This research examines the historical arrival of Islam in Pagaran Bira Jae Village, Padang Lawas Regency, North Sumatra, and explores its development in the realms of economics, education, and Islamic heritage. The arrival of Islam in this area is significant, as Pagaran Bira Jae was one of the first regions in Padang Lawas to embrace the religion. The spread of Islam in Pagaran Bira Jae is closely tied to trade activities, and prominent religious figures like Sheikh Jired and Malim Mudo I played a crucial role in its dissemination. The research also links the Padri War and the influence of West Sumatran and Tapanuli ulama in shaping religious growth. In terms of physical heritage, Pagaran Bira Jae and Pagaran Bira Julu house several religious institutions, including mosques, surau, and madrasahs, as well as Islamic relics such as the tomb of a saint named Jired, which bears Arabic inscriptions and Pallawa script, possibly from Gujarat, India. This study employs historical methods to provide a comprehensive understanding of the local Islamic legacy.